Research on dynamic simulation and prediction of urban expansion based on SLEUTH model. (10th November 2020) - Niu, Lede; Pan, Mei; Zhou, Yan
In order to improve the accuracy of traditional prediction methods in the analysis of urban expansion, the method for dynamic simulation of urban expansion based on SLEUTH (slope, land use, urban area, traffic, exclusion, hillshead) model is proposed. The method uses processed urban spatial data to establish a SLEUTH model of dynamic urban expansion, and it analyses the driving factors of urban expansion that are used as the influencing factor of urban expansion simulation. Through dynamic simulation, the law of urban expansion is derived and input SLEUTH model as the law of free expansion. The influencing factors are input into the model, and the prediction results are obtained with the law of free expansion. The experimental result shows that the new method has a prediction error rate of only 3.5% with the low delay and the strong reliability, compared with the traditional urban expansion prediction method.